From inclusion to inclusivity: A scoping review of community music scholarship. Issue 2 (1st August 2019) - Yerichuk, Deanna; Krar, Justis
This article investigates how community music scholarship has taken up inclusion. Using a modified scoping review methodology, the authors analysed 47 articles published in the International Journal of Community Music from 2008 to 2018, examining how scholars have defined and operationalized the terms 'inclusion' and 'inclusivity', which were used interchangeably in the literature. The authors found that inclusion was often normatively invoked with no definition or approaches provided. In those articles that provided more detail about inclusion, many focused on musical access, such as removing auditions and not requiring previous music skill or knowledge, and processes of musical inclusion, such as creating a friendly and non-judgmental atmosphere, providing multiple ways of engaging with music-making and cultivating musical leadership among participants. Less frequent in the literature were ideas and approaches focusing on social inclusion through music, including frameworks that aimed to address and change systems that create marginalization; approaches that addressed social barriers to participation, such as transportation and childcare; and approaches that decentralized leadership to create collective responsibility and participation. The authors conclude by examining approaches from other scholarly disciplines, arguing that community music scholarship may benefit for more sustained and deliberate use of the term inclusivity, which points to the ongoing practice and effort towards inclusion.